Efficient Control of Zika Virus Infection Induced by a Non-Replicating Adenovector Encoding Zika Virus NS1/NS2 Antigens Fused to the MHC Class II-Associated Invariant Chain - Loulieta Nazerai (MDPI AG, 2021)
It is generally believed that a successful Zika virus (ZIKV) vaccine should induce neutralizing antibodies against the ZIKV envelope (E) protein to efficiently halt viral infection. However, E-specific neutralizing antibodies have been implicated in a phenomenon called antibody-dependent enhancement, which represents an ongoing concern in the flavivirus-vaccinology field. In this report, we investigated the vaccination potential of replication-deficient adenoviral vectors encoding the ZIKV non-structural proteins 1 and 2 (NS1/NS2) and employed the strategy of linking the antigens to the MHC-II associated invariant chain (li) to improve immunogenicity and by inference, the level of protection. We demonstrated that li-linkage enhanced the production of anti-NS1 antibodies and induced an accelerated and prolonged polyfunctional CD8 T cell response in mice, which ultimately resulted in a high degree of protection against ZIKV infection of the CNS.